Bullous aplasia cutis congenita: A report of two cases and brief review of the selected literature - Prćić Sonja; Matić Aleksandra; Jablanović Slađana; Matić Milan; Gajinov Zorica; Stašuk Nataša (Vojnosanitetski Pregled)
Introduction. Aplasia cutis congenita (ACC) is a rare condition characterized by the focal absence of skin, and sometimes other underlying structures at birth. It may occur as an isolated defect or associated with other anomalies and defects. Bullous ACC (BACC) is a clinical subtype of the condition with few cases reported in the literature. It presents as a bullous lesion at birth which gradually transforms into an atrophic scar covered by a thin epithelial membrane. It is considered as cutaneous sign of possible neural tube dysraphism. Some cases present with a dark hair around the lesion (the hair collar sign), which can be even more indicative of neural tube defect. However, cases of BACC reported till today are inconclusive regarding this connection. Case report. We report a two cases of BACC of the scalp, in one patient associated with hair collar sign without neural tube defects and the other with hemangioma and we give a brief review of the selected literature. Conclusion. Bullous or membranous aplasia cutis congenita is benign condition, but may represent as a cutaneous marker of occult neural tube defect. Recognising the condition is important in order to rule out associated anomalies.